Parceirão de que jornada? Memes LGBT+ e humor no Twitter/X em 2023 - Rodrigues, Tiago Augusto (2025)
This study aims to identify and analyze memes related to the LGBT+ population which circulated on the digital social media platform Twitter/X during 2023, with an emphasis on understanding the discursive practices and interpretative repertoires associated with these cultural objects. The exploratory phase of this research was conducted using the researcher’s account on the platform, culminating in the identification of 41 distinctive memes related to the LGBT+ community. These objects were collected and organized not as isolated pieces but as interconnected elements of a collection. The analysis adopted an interdisciplinary approach, grounded in the methodology of discursive practices and construction of meaning in everyday contexts, originating in social psychology. This perspective made it possible to understand how memes function as instruments of cultural expression, resistance, and identity resignification. Among the main themes identified are the reproduction and contestation of stereotypes about the LGBT+ population, as well as the discursive approaches surrounding same-sex unions, both of which are explored in depth. The results revealed that the analyzed memes mobilize diverse repertoires, ranging from ironic humor to social critique, fostering reflections on cis-heteronormativity and reinforcing the importance of visibility and belonging for this population within the digital landscape. The study of specific cases, such as the "Parceirão de Jornada" meme, demonstrated how the re-signification of these objects contributes to symbolic resistance and the construction of affective narratives. It is concluded that memes not only reflect but also transform social and cultural practices, They play a significant role in the production and circulation of meanings related to the LGBT+ population. The findings of this study provide significant contributions to the fields of digital communication and identity studies, while also highlighting gaps and promising avenues for future research on the impact of discursive practices in digital environments.